THE EFFECT OF SARULLA NATURAL NANOZEOLITE ADDITION IN THE PREPARATION OF NANOCOMPOSITE FOAM POLYURETHANTSVIEWED FROM FTIR CHARACTERIZATION - Fransiskus Gultom; Hernawaty Hernawaty (Jurnal Darma Agung, 2020)
The fabrication and characterization of polyurethane foam nanocomposites with the addition of Sarulla natural nanozeolite fillers has been investigated. The steps carried out in research on the manufacture of polyurethane foam nanocomposites are: 1) Preparation and purification of natural zeolites, 2) Preparation of nanozeolites, and 3) Preparation of polyurethane foam nanocomposites is carried out using an in situ process by mixing natural nanozeolites in a mixture of polypropylene glycol and toluene diisocyanate. The results of the particle size analyzer show Sarulla nanozeolite particle size is 95.8 nm. The XRF results showed that the main composition of Sarulla nanozeolites was SiO2 (80.98%) and Al2O3 (14.21%), while the XRD results showed that Sarulla nanozeolites were Mordenite types. Variation in weight ratio of nanozeolites as fillers to polypropylene glycol and toluene diisocyanate is (0, 5, 10, 15, 20 and 25)%. The results of the FTIR spectrum of polyurethane foam and polyurethane foam nanocomposite show almost the same functional groups, this is caused by the interaction that occurs between polyurethane foam and nanozeolite is a physical reaction.